Pemikiran Pendidikan Pluralisme Keagamaan Ahmad Syafii Maarif - Arrohmawati, Fajrul Amalia, Dr. Mutohharun Jinan, M.ag (2017)
Indonesia is an archipelagic nation that compounds customs, tribes and religions. Religion becomes the principle of the right to live as a citizen and to worship the Lord is neither negoitable nor prohibited by anyone. However, the trust faiths often violate the rights of other religions in the practice of religion in Indonesia since the first until today. Departing from such backgrounds the author then, will rediscuss the thinking of Muslim leaders who tries to formulate the idea of religious tolerance, namely Ahmad Syafii Maarif, and therefore the author tooks the title "Religious Pluralism Education Thoughts of Ahmad Syafii Maarif". This study aims to obtain information about the educational thought of religious pluralism by Ahmad Syafii Maarif, and its implications. The research uses descriptive qualitative approach, based on literature and the historical method. While the method of data collection uses the method of documentation and analysis of data uses the content analysis method. With that framework, it is known that the principle of honesty, sincerity, tolerance and promoting the human values is indispensable in the hold of religious pluralism education. Furthermore, it is necessary to have attitude of adherence to the constitution in order to care for diversity and avoid from being narrow fanaticism. Educational implications of religious pluralism of Ahmad Syafii Maarif include two sides. In the internal side, the theme of morality and tolerance are the missions that he always brings, and in the external side, through his thoughts he immediately shares and Maarif Institute he has established, the idea of pluralism is increasingly known and widely spread into the minds of the people of Indonesia. Keywords: Religious Pluralism, Education, Ahmad Syafii Maarif .